(untitled) - Bateman, Thomas S. (Boston, 2007)
Bateman and Snell have consistently discussed and explained the traditional, functional approach to management through planning (delivering strategic value), organizing (building a dynamic organization), leading (mobilizing people), and controlling (learning and changing). Management: Leading And Collaborating in a Competitive World retains its series of "firsts": first to have a chapter on diversity, first to devote a section to the natural environment, and first to relate a "bricks and clicks" theme to explain the challenges of managing in a New Economy. This new edition is no exception with an emphasis on leadership and collaboration as a means to success.
Keywords: Management,Quản lí